The Impact of Social Media Content on Teenagers Needs Parental and Government Oversight - Vicki Dwi Purnomo; Syarofi (PT FORMOSA CENDEKIA GLOBAL, 2023)
Dissemination of Positive and Negative Information Among Teenagers. As for the background of the problem, the dissemination of information has sometimes deviated from legal and customary provisions and even violated religious rules. For example, young people post photos of holding hands with partners who are not mahram, besides that there is also the attitude of some young people spreading false information such as narcissistic photos which are sometimes fun to show the strengths they have, or publicize the good they have done. , for example posting clothes or luxury vehicles, selfies at places of recitation or places of preaching and so on. That the information disseminated is very dependent on the information obtained. Because the Teunom people represent what they get from social media, if the information they get is good, it will be good to spread it and vice versa.